Dukungan Informasi Perawat terhadap Kecemasan Keluarga Pasien Stroke: The Nurse Information Support on the Anxiety of Stroke Patients' Families at I. A. Moeis Hospital Samarinda - Kanti, Surti; Era, Dwi Prihatin; Wiyadi, Wiyadi (Jurnal Diskursus Ilmiah Kesehatan, 2024)
Background: Stroke is a non-communicable disease with the largest contributor to death and disability worldwide. In developed countries as well as developing countries. East Kalimantan Province includes the highest prevalence of stroke nationally in Indonesia. The impact of stroke in addition to patients also causes psychological anxiety for the patient's family from the family's unpreparedness in caring for stroke patients. Family anxiety can be overcome through the role of nurses in providing motivation and support to families caring for stroke patients in the support of information about stroke through counseling. Objective: To determine the effect of nurse information support on the anxiety of stroke patients' families at RSUD I. A Moeis Samarinda. Method : The research design uses quasi experimental design without control group conducted in August – September 2023 at RSUD I.A Moeis Samarinda, East Kalimantan, Indonesia. A total of 56 people were involved as samples based on purposive sampling by determining inclusion and exclusion criteria. Data were collected using the HARS anxiety questionnaire and analyzed with the Wilcoxon Signed Ranks Test. Results : The results showed that the average value of anxiety decreased from 85.46 (pre) to 74.09 (post) with a difference of 11.37 points with a Z table of -6.513 and p value = 0.000. Conclusion : There is an effect of nurse information support on the anxiety of stroke patients' families at RSUD I. A Moeis Samarinda. These findings become basic data in the development of family nursing, so that in the process of patient care, families are also involved and educated about disease and treatment management and care.